Dimensi Matriks Dan Dimensi Partisi Pada Graf Hasil Operasi Korona (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2016)
Let????(????,????)is a connected graph.For an ordered set ????={????1,????2,…,????????} of vertices, ????⊆????(????), and a vertex ????∈????(????), the representation of ???? with respect to ???? is the ordered k-tuple ????(????|????)={????(????,????1),????(????,????2),…,????(????,????????)|∀????∈????(????)}. The set W is called a resolving set of G if every vertex of G has a distinct representation. A resolving set containing a minimum number of vertices is called a basis for ????. The metric dimension of ????, denoted by ????????????(????), is the number of vertices in a basis of ????. Then, for a subset S of V(G), the distance between u and S is ????(????,????)=????????????{????(????,????)|∀????∈????,∀????∈????(????)}. Let Π=(????1,????2,…,????????)be an ordered l-partition of V(G), for∀????????⊂????(????) dan????∈????(????), the representation of v with respect to Π is the l-vector ????(????|Π)=(????(????,????1),????(????,????2),…,????(????,????????)). The set Π is called a resolving partition for G if the ????−vector ????(????|Π),∀????∈????(????)are distinct. The minimum l for which there is a resolving l-partition of V(G) is the partition dimension of G, denoted by ????????(????). In this paper, we determine the metric dimension and the partition dimension of corona product graphs ????????⨀????????−1, and we get some result that the metric dimension and partition dimension of ????????⨀????????−1respectively is????(????−2) and 2????−1, for????≥3.Keyword: Metric dimention, partition dimenstion,corona product graphs